2011
DOI: 10.1186/1745-6215-12-59
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on patients with fibromyalgia: study protocol of a multicentre randomized controlled trial

Abstract: BackgroundFibromyalgia is a multidimensional disorder for which treatment as yet remains unsatisfactory. Studies of an acupuncture-based approach, despite its broad acceptance among patients and healthcare staff, have not produced sufficient evidence of its effectiveness in treating this syndrome. The present study aims to evaluate the effectiveness of individualized acupuncture for patients with fibromyalgia, with respect to reducing their pain and level of incapacity, and improving their quality of life.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(41 reference statements)
0
4
0
1
Order By: Relevance
“…32 In order to evaluate the influence of family structure, a semi-structured interview, incorporating the genogram technique, was performed. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In order to evaluate the influence of family structure, a semi-structured interview, incorporating the genogram technique, was performed. 27 …”
Section: Discussionmentioning
confidence: 99%
“…27 The SA group received an acupuncture simulation on the dorsal and lumbar regions, in which guide tubes for the same type of needle as used in the real acupuncture group were applied to the body surface, but after removal of the needles. 27 The time devoted to the treatment and evaluation of participants was identical in both groups.…”
Section: Interventionsmentioning
confidence: 99%
“…We speculate that while inflammation was reduced, it was not eliminated, and thus, inflammatory mediators could continue to activate nociceptors to produce nociceptive behaviors. Clinically, MA is effective in a variety of pain conditions, including neuropathic pain [47], knee osteoarthritis [45,48,49], acute and chronic back pain [49], and fibromyalgia [50]; however, there is a large variability in the acupoints used. Thus, it is possible that a different protocol of MA would be more effective in each of these different models.…”
Section: Discussionmentioning
confidence: 99%
“…Despite wide acceptance among patients and health professionals, evidences on the efficacy of acupuncture in the treatment of FMS are yet lacking. Vas et al [ 30 ] randomized 156 FMS patients to either real or sham acupuncture groups and concluded that it might provide evidence on the efficacy of acupuncture as a therapeutic option for FMS in patients with and without severe depression. Similar to our study design, in another study, Martin et al [ 31 ] randomized 50 fibromyalgia patients to either real or sham acupuncture groups and found that acupuncture significantly resolved fibromyalgia symptoms, compared to placebo, and that the most notable resolution was observed in fatigue and anxiety during follow-up.…”
Section: Discussionmentioning
confidence: 99%